Strategic Organizational Management in 'The Black' Volleyball Club Majalengka - Purnama, Yudhi; Sahudi, Udi (Indonesian Journal of Sport Management, 2024)
"The Black" volleyball club is a sports entity that aims to compete in competitions and strengthen its financial sustainability. Strategic organizational management is the key to long-term success in facing competitive dynamics and environmental changes. This study explores effective strategic organizational management practices in the context of "The Black" volleyball club, including vision formulation, goal setting, external and internal environmental analysis, competitive strategy development, and strategy implementation and evaluation. Data will be collected through qualitative interviews with managers, players, and club staff and analysis of related documents. The results of this research will likely provide valuable insights for other sports clubs in managing their organizations effectively and sustainably.